2021
DOI: 10.1186/s12866-021-02092-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison and interpretation of characteristics of Rhizosphere microbiomes of three blueberry varieties

Abstract: Background Studies on the rhizosphere microbiome of various plants proved that rhizosphere microbiota carries out various vital functions and can regulate the growth and improve the yield of plants. However, the rhizosphere microbiome of commercial blueberry was only reported by a few studies and remains elusive. Comparison and interpretation of the characteristics of the rhizosphere microbiome of blueberry are critical important to maintain its health. Results … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 64 publications
1
8
0
1
Order By: Relevance
“…The varied compartment niches affected the proportions of the root-associated microbial community composition of blueberry. Consistent with previous studies, Actinobacteria and Proteobacteria were the most abundant phyla in the bacterial community ( 22 ), and our results showed that Actinobacteria was the dominant phylum in the endosphere. Members of Actinobacteria possess a potential suppressive effect on plant pathogens ( 53 ), and the increased proportion in the endosphere may have been related to the selection of functions that correspond to plant health requirements.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The varied compartment niches affected the proportions of the root-associated microbial community composition of blueberry. Consistent with previous studies, Actinobacteria and Proteobacteria were the most abundant phyla in the bacterial community ( 22 ), and our results showed that Actinobacteria was the dominant phylum in the endosphere. Members of Actinobacteria possess a potential suppressive effect on plant pathogens ( 53 ), and the increased proportion in the endosphere may have been related to the selection of functions that correspond to plant health requirements.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, ericoid mycorrhizal (ERM) fungi can form symbiotic relationships with blueberry roots that can play a critical role in the survival of plants growing in habitats with low soil pH and slow organic matter turnover by secreting a broad range of enzymes, including cellulases, proteases, polyphenol oxidases, and phosphatases, which decompose complex organic compounds and enhance the fitness and nutrient acquisition of the host plant ( 18 20 ). Several studies have focused on the impact of host cultivars ( 21 23 ), differential habitats ( 16 , 24 , 25 ), and agricultural practices ( 26 ), but further exploration of the interactions of blueberry root-associated microorganisms along the soil-rhizosphere-root continuum is needed.…”
Section: Introductionmentioning
confidence: 99%
“…For the collection of rhizosphere soil samples, refer to a prior article. 23 Specifically, the rhizosphere soil was quickly collected by gently brushing the remaining soil sticking on the roots (the rhizosphere soil was 3−5 mm above the roots) with brush pencils. Rhizosphere soil samples were collected in five parallels.…”
Section: Field Experiments Designmentioning
confidence: 99%
“…Kelompok Bacillus, Pseudomonas, Aspergillus, Fusarium, dan Colletotrichum dapat ditemukan pada rhizosfer tanaman stoberi (Putra et al, 2020). Tingkat keanekaragaman yang berbeda juga ditemukan sampai pada tingkat varietas tumbuhan seperti yang ditemukan pada blueberry (Zhang et al, 2021).…”
Section: Pendahuluanunclassified